Program promosi kesehatan terhadap pengetahuan dan sikap dalam pencegahan stunting - Ari Yunita; Umi Romayati Keswara; Linawati Novikasari (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Background: Stunting is a nutritional status that occurs when a child has a height or length of <-20 standard deviation. Based on 2018 basic health research, 30.8% of children under five are stunted. The health profile of the Lampung Province service in 2018 27.28 children were stunted, stunting was caused by several factors, one of which was a lack of knowledge of mothers about health and nutrition so that mothers could not take a stand in preventing stunting.Purpose: To Knowing the effect of stunting prevention health education on knowledge and attitudes of the mothers Method: This type of quantitative research is pre-experimental one-group pre-post test. The population in this study were mothers who had babies aged 0-24 months with a total of 20 people. Data analysis used the Wilcoxon test. Results: statistical tests using the Wilcoxon test for maternal knowledge, obtained a p-value of 0,000 so that the p-value <α (0,000 <0.05) then H0 is rejected and the attitude statistics using Wilcoxon is obtained p-value 0,000 so that the p-value <α (0,000 <0 , 05) then H0 is rejected.Conclusion: There is an effect of stunting prevention health education on the knowledge and attitudes of mothersKeywords: Prevention; Stunting; Knowledge; AttitudePendahuluan: Stunting merupakan status gizi yang terjadi apabila seorang anak memiliki tinggi atau panjang badan ±20 standart deviasi. Berdasarkan riset kesehatan dasar 2018 30,8% balita mengalami stunting. Profil kesehatan dinas Provinsi Lampung Tahun 2018 27,28 anak mengalami stunting, stunting disebabkan oleh beberapa faktor salah satunya kurangnya pengetahuan ibu mengenai kesehatan dan gizi sehingga ibu tidak dapat mengambil sikap dalam mencegah terjadinya stunting.Tujuan: Diketahui pengaruh pendidikan kesehatan penceghan stuntiing terhadap pengetahuan dan sikap ibu Metode: Rancangan penelitian pre-experiment dengan pendekatan one-group pre-post test design. Populasi dalam penelitian ini adalah ibu yang memiliki bayi usia 0-24 bulan dengan jumlah sampel 20 partisipan. Analisis data menggunakan uji Wilcoxon.Hasil: Didapatkan pengaruh pendidikan kesehatan terhadap pengetahuan dengan p-value 0,000 <0,05 sedangkan terhadap sikap didapat p-value 0,000 <0,05Simpulan: Ada pengaruh pendidikan kesehatan pencegahan stunting terhadap pengetahuan dan sikap ibu